2015
DOI: 10.3201/eid2110.150380
|View full text |Cite
|
Sign up to set email alerts
|

Heartland Virus Neutralizing Antibodies in Vertebrate Wildlife, United States, 2009–2014

Abstract: Since its discovery in 2009, the tickborne Heartland virus (HRTV) has caused human illness in Missouri, Oklahoma, and Tennessee USA. To better assess the geographic distribution of HRTV, we used wildlife serology as an indicator. This retrospective evaluation determined that HRTV is widespread within the central and eastern United States.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
65
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(68 citation statements)
references
References 11 publications
2
65
0
1
Order By: Relevance
“…The disease course was protracted with the majority of animals surviving the infection. The generally less severe HRTV infection in the immune deficient STAT2 KO hamsters is consistent with the idea that the virus, despite evidence of its presence across many eastern states (Bosco-Lauth et al, 2015; Riemersma and Komar, 2015), seldom causes severe disease that would require hospitalization in healthy individuals.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The disease course was protracted with the majority of animals surviving the infection. The generally less severe HRTV infection in the immune deficient STAT2 KO hamsters is consistent with the idea that the virus, despite evidence of its presence across many eastern states (Bosco-Lauth et al, 2015; Riemersma and Komar, 2015), seldom causes severe disease that would require hospitalization in healthy individuals.…”
Section: Discussionsupporting
confidence: 80%
“…HRTV was first isolated in Missouri in 2009 from two hospitalized farmers that presented with fever, fatigue, diarrhea, leukopenia, and thrombocytopenia (McMullan et al, 2012). With less than a dozen cases reported and serological evidence of widespread prevalence of HRTV across central and eastern US (Bosco-Lauth et al, 2015; Riemersma and Komar, 2015), the virus appears to be less virulent than SFTSV causing mostly subclinical or mild illness. Death associated with HRTV disease appears to be linked to advancing age and underlying conditions that likely exacerbate the infection and disease process (2014; Fill et al, 2016; Muehlenbachs et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…High seroprevalence rates for HRTV have been reported in northern raccoons ( Procyon lotor ), white-tailed deer ( Odocoileus virginianus ), and horses sampled near the residences of human case-patients ( 3 ). Additional serosurveillance in wildlife has demonstrated wide-ranging antibody prevalence to HRTV across the geographic host range distribution of A. americanum ticks ( 4 ). …”
mentioning
confidence: 99%
“…Using the same method, Xing et al found that seroprevalence ranged from 10% to 18% in samples from cattle, sheep, goats, deer, and elk in 24 Minnesota counties of the USA [30]. A possible cross-reaction with Heartland virus, which is phylogenetically related to HYSV and extensively identified in USA, should be considered when interpreting this result [31].…”
Section: Domestic Animals Are Widely Infectedmentioning
confidence: 85%